2017
DOI: 10.7554/elife.31186
|View full text |Cite
|
Sign up to set email alerts
|

The P2X7 receptor forms a dye-permeable pore independent of its intracellular domain but dependent on membrane lipid composition

Abstract: The P2X7 receptor mediates extracellular ATP signaling implicated in the development of devastating diseases such as chronic pain and cancer. Activation of the P2X7 receptor leads to opening of the characteristic dye-permeable membrane pore for molecules up to ~900 Da. However, it remains controversial what constitutes this peculiar pore and how it opens. Here we show that the panda receptor, when purified and reconstituted into liposomes, forms an intrinsic dye-permeable pore in the absence of other cellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
128
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(154 citation statements)
references
References 82 publications
(109 reference statements)
11
128
0
Order By: Relevance
“…Yet, on a closer look, what this mutation seems to do in the study by Adinolfi et al (2010) is simply to reduce the small (Ca 21 ) and large (YoPro-1) cation uptake in a comparable way; in conjunction with the results of a previous study performed with another carboxyl terminal truncated P2X7R , it looks as though this truncation reduces the overall activity of the receptor. Such a loss in P2X7R activity with carboxyl tail deletion is also suggested by the findings of Karasawa et al (2017).…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…Yet, on a closer look, what this mutation seems to do in the study by Adinolfi et al (2010) is simply to reduce the small (Ca 21 ) and large (YoPro-1) cation uptake in a comparable way; in conjunction with the results of a previous study performed with another carboxyl terminal truncated P2X7R , it looks as though this truncation reduces the overall activity of the receptor. Such a loss in P2X7R activity with carboxyl tail deletion is also suggested by the findings of Karasawa et al (2017).…”
Section: Introductionmentioning
confidence: 54%
“…In another study, carboxyl terminal truncation of P2X7R was claimed not to affect the ionic currents but abolish the dyeuptake (Smart et al, 2003). However, the use of different cell types to measure ionic currents (oocytes) and the dye uptake (HEK-293) seems to be a major drawback of this study, as the magnitude of the functional loss caused by the truncation was later shown to change in a complicated way, depending on the membrane lipid composition or the cell type (Karasawa et al, 2017).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Nucleotides are an important class of signaling molecules in the nervous system, what was discovered already fifty years ago (Burnstock, 1972;Burnstock, 2007). ATP and other extracellular nucleotides released by neurons (Lopatář et al, 2015) as well as glia (Illes et al, 2019) are responsible for the communication between different CNS cells (Abbracchio et al, 2009): metabotropic, G-coupled P2Y receptors (Abbracchio et al, 2006;von Kügelgen, 2019) and P2X receptors which serve as plasma membrane ion channels (Kawate, 2017). All nucleotide receptors are characterized by different ligand affinity and downstream signaling properties.…”
Section: Introductionmentioning
confidence: 99%
“…Some reports suggest a role of another protein -pannexin-1 -in this process (Xu et al, 2012), while others claim that dilation of the P2X7 channel is sufficient for the pore opening and may be an effect of cell swelling (Anastacio Alves et al, 2014). Recent work revealed also a possible role of plasma membrane lipids in the pore formation (Karasawa et al, 2017).…”
Section: Introductionmentioning
confidence: 99%